2020
DOI: 10.1371/journal.pone.0233096
|View full text |Cite
|
Sign up to set email alerts
|

Association between single nucleotide polymorphisms (SNPs) of IL1, IL12, IL28 and TLR4 and symptoms of congenital cytomegalovirus infection

Abstract: Congenital cytomegalovirus (cCMV) infection is the most common intrauterine infection. A non-specific immune response is the first line of host defense mechanism against human cytomegalovirus (HCMV). There is limited data on associations between Single Nucleotide Polymorphisms (SNPs) in genes involving innate immunity and the risk and clinical manifestation of cCMV infection. The aim of the study was to investigate association between selected SNPs in genes encoding cytokines and cytokine receptors, and predis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 44 publications
0
18
1
1
Order By: Relevance
“…Eight selected SNPs were genotyped successfully in the study population [ 33 ]. The genotypic frequencies of SNPs for the overall study population are shown in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eight selected SNPs were genotyped successfully in the study population [ 33 ]. The genotypic frequencies of SNPs for the overall study population are shown in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…We prospectively enrolled Caucasian neonates with confirmed cCMV admitted into the Neonatal Intensive Care Unit of The Children’s Memorial Health Institute in Warsaw between 2016 and 2019 [ 33 ]. Inclusion criteria were positive real-time PCR DNA CMV in urine ≤ 21st day of life, and parental consent.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…No estudo é apresentada a relação entre o polimorfismo da IL12B rs3212227 e o risco reduzido de um nascimento prematuro, a partir de sua participação na defesa imunológica do hospedeiro contra infecções, já que a IL-12 é uma citoquina inflamatória responsável por influenciar as células Th1. Esse é um estudo recente e pioneiro acerca desse assunto, trazendo associações entre SNPs nos genes IL1B, IL12B, IL28B, TLR4 e os sintomas da infecção por cCMV como prematuridade, esplenomegalia, trombocitopenia e hepatite respectivamente (Jedlińska-Pijanowska et al, 2020).…”
Section: Citomegalovírusunclassified